Palaeoecology and Palaeoenvironments of Late Cenozoic Mammals : Tributes to the Career of C.S. (Rufus) Churcher - Seymour, Kevin L.; Churcher, C. S., 1928-; Stewart, Kathlyn Moore (Book collections on Project MUSE., 2018)
The papers focus on late Cenozoic mammals in North America and Africa and provide both site-specific descriptions of faunas and their associated geological contexts, and more general syntheses of regional palaeoenvironments and biogeography.